PENGARUH MEDIA BONEKA JARI TERHADAP KEMAMPUAN BERBICARA DI TAMAN KANAK-KANAK PUTIH ASRI KAMBOJA KABUPATEN PESISIR SELATAN - Bella Putri Bungsu, Yul Syofriend; Nenny Mahyuddin, Tisna Syafnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The significance of fostering the growth of children's language abilities at Putih Asri Kamboja Kindergarten is what drives this research. Media including finger puppets are offered to youngsters since speaking is crucial in everyday life. When children play with finger puppets, it helps them develop their language skills, particularly their speaking abilities, which allow them to express themselves verbally. The purpose of this research is to find out how the Putih Asri Kamboja Kindergarten students' language skills were affected by the use of finger puppets. When kids learn to talk, they begin to be able to articulate more complex ideas and emotions. A quantitative method based on a quasi-experiment design is employed in this work. All kindergarteners at Putih Asri Kamboja make up the population, while fifteen kids from B1 and B2 make up the sample. Interviews, documentation, and organized observation are some of the methods used to gather data. A few methods used in data analysis include the hypothesis test, the homogeneity test, and the normalcy test. We utilized a statement sheet to gather data, then we ran the t-test on it in SPSS 16.0 for Windows. The findings of the data analysis revealed that the children's speaking abilities in the experimental class exhibited changes while utilizing finger puppet media compared to the control class, which used hand puppets. The control group averaged 14.93 on the pretest, whereas the experimental group achieved 15. The experimental group averaged a post-test score of 26, whereas the control group averaged 24.26. Results from both the pre- and post-tests showed that the experimental group achieved an average gain score of 26.00, whereas the control group had an average gain score of 24.27. The significance value, with two tails, was less than 0.05, at 0.03. So, the two groups— the control and the experimental—are quite different. That being the case, we can accept Ha as the alternative hypothesis and reject H0. Research like this demonstrates that media including finger puppets can influence kids' verbal development.